Modern Directions in School Buildings Formation - Kutstevych, Vadym; Rusin, Volodymyr; Tyshkevych, Olga (International Journal of Engineering and Technology, 2018)
The purpose of the article is to identify modern areas in designing the network and buildings of general secondary education institutions on the example of Ukraine. In the course of the research, the preconditions for forming the network and buildings of different school types were analyzed. In particular, the existing network, material and technical base of schools were considered, their features were revealed. Based on the study of modern socio-pedagogical and architectural and urban factors, the requirements for the architectural and planning organization of school buildings have been identified. It was established that the existing material and technical base of general secondary education institutions does not fully meet these requirements. The generalization of the theory and practice of the school buildings formation in developed countries of the West, Ukraine and the countries of the post-Soviet space allowed to identify the latest trends in the design of general secondary education institutions. The authors provided suggestions on the territorial educational districts formation as a promising direction for improving the school network. The perspective types of general secondary education institutions, which are formed on the basis of interagency integration with other objects of cultural and household services, are revealed. Methods of school buildings architectural and planning organization that meet the modern educational process requirements are developed.Â Â Â